Metrology, Inspection, and Process Control for Microlithography XXIII 2009
DOI: 10.1117/12.814466
|View full text |Cite
|
Sign up to set email alerts
|

Study of advanced mask inspection optics with super-resolution method for next-generation mask fabrication

Abstract: The lithography potential of an ArF (193nm) laser exposure tool with high numerical aperture (NA) will expand its lithography potential to 45nm node production and even beyond. Consequently, a mask inspection system with a wavelength nearly equal to 193nm is required so as to detect defects of the masks using resolution enhancement technology (RET). A novel high-resolution mask inspection platform using DUV wavelength has been developed, which works at 199nm. The wavelength is close to the wavelength of ArF ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[1]- [3] We have also proved the inspection sensitivity characteristics of C-pol, Ppol, and S-pol illuminations with the proof machine NT-7000α in joint research with Selete [4] . Based on these results, the optical system in NPI-7000 is equipped with a reflection C polarized inspection mode, a reflection P polarized inspection mode, and a reflection-reflection P/S concurrent inspection mode.…”
Section: Opticsmentioning
confidence: 94%
See 1 more Smart Citation
“…[1]- [3] We have also proved the inspection sensitivity characteristics of C-pol, Ppol, and S-pol illuminations with the proof machine NT-7000α in joint research with Selete [4] . Based on these results, the optical system in NPI-7000 is equipped with a reflection C polarized inspection mode, a reflection P polarized inspection mode, and a reflection-reflection P/S concurrent inspection mode.…”
Section: Opticsmentioning
confidence: 94%
“…It is also known that phase defects in EUV blanks can be detected by the variance in reflection intensity of the 199nm wavelength light source, and we have previously demonstrated that these detection signals can be enhanced by using focus offsets [4] [5] .Our NPI-7000 incorporates two different sensors that can be used in de-focus mode to simultaneously obtain the reflection images to inspect the EUV mask blanks. Figure 4 shows the outline of the optics system.…”
Section: Opticsmentioning
confidence: 97%